IMPACT OF AFFORDABLE SENIOR HOUSING-BASED SERVICES ON MEDICARE EXPENDITURES. (11th November 2018) - Sanders, A; Stone, R I; Kandilov, A; Richa Siegfried, N; Keyes, V
Abstract: The Support and Services at Home (SASH) program in Vermont is an affordable senior housing-based service program that aims to coordinate care and assist low-income participants in accessing the health care and support services they need to maintain health and age comfortably and safely in their homes. Our study examined the impact of the first five-and-a-half years of the SASH program on the Medicare expenditures of these participants. Using a difference-in-differences model, we compared the change in expenditures among SASH participants with the change in expenditures for a comparison group living in affordable senior housing properties that did not host the SASH program. Findings indicate that participants in urban panels experienced a reduction in the rate of growth in total Medicare expenditures of $122.24 per beneficiary per month ($1, 466.88 annually) and expenditures for hospital care, emergency department visits, and specialist physician visits relative to the comparison group.